Effects of Mineral Elements on the Environment - Pinto, Marina Cabral; Kumar, Amit (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Medical mineralogy and geochemistry constitute an important field, yet little attention has been paid to it by scientists, administrators, or the public. The aims of this book are: (a) to focus on a selection of current challenges and research opportunities and (b) to encourage knowledge transfer between geochemists and mineralogists whose work concerns medical problems and medical scientists who study problems surrounding biominerals and geomaterials. This book covers a variety of novel approaches, tools and techniques, and scenarios of contamination in water and wastewater, and is a key resource for policymakers and environmental scientists working hard to address environmental pollutants. The key features are: state-of-the-art techniques for the assessment and remediation of heavy metals, presenting the interdisciplinary impacts of heavy metals, including those on human health, ecosystems and water quality, and including various contamination indices, such as contamination factor, geoaccumulation index, enrichment factor, pollution index and ecological risk index.